Money in finance - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
This paper begins by defining, and distinguishing between, money and finance, and addresses alternative ways of financing spending. We next examine the role played by financial institutions (e.g., banks) in the provision of finance. The role of government as both regulator of private institutions and provider of finance is also discussed, and related topics such as liquidity and saving are explored. We conclude with a look at some of the new innovations in finance, and at the global financial crisis, which could be blamed on excessive financialization of the economy.
Keywords: B14; B15; B22; B52; E12; E40; E42; E50; E51; E52; G14; G21; 330; money; money of account; finance; financial instruments; financial institutions; financial innovation; financialization; liquidity; saving; state money; chartalism; shadow bank; Hyman Minsky; securitization; Robert Clower